The Principles of Science and Technology in the Development of Islamic Religious Education Curriculum - Sihombing, Sulaiman; Utami Daulay, Aisyah Futri (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
Islamic religious education faces the challenge of disruption in the era of the industrial revolution 4.0. The development of digital science and technology means that everyone can access all types of information and connect quickly through the internet and its innovations (internet of things). The effects of technology have both positive and negative potential for humans. Islamic religious education must be able to prepare human resources who have faith and morals and become Muslim intellectuals. The development of the Islamic education curriculum is an effort to face challenges in the era of the industrial revolution 4.0 which is synonymous with sophisticated information technology. This study uses the library method by collecting and analyzing library data. The results of the study show the need to adjust the Islamic religious education curriculum in the current digital era, from the goal of Islamic education, which is to make educated people become Muslim intellectuals, learning methods using a combination of conventional and technology, namely blended learning, the content of the material must be adjusted to the circumstances and skills needs of the 4.0 era, comprehensive evaluation and shared responsibility (educational ecosystem). Educators must adapt and have the competencies needed in the digital era and infrastructure that is adapted to technological developments. which is synonymous with advanced information technology.